(Moriscons and Inquisition in Spain (1492- 1614 - Al- Rubaihat, Mahmoud Saleh; Al- Jazi, Mohammed Abdulhadi; Al.shogairat, Hussein Raja (Journal of Humanities & Social Sciences, 2020)
The Moricissue is one of the most sensitive topics in the study of the history of Arabs and Muslims in general, and of Morocco in particular. The tragedy of the Moriscans and the fall of Granada is a source of condemnation of the Arab conscience. They also call for the shame and shame of abandoning Muslims in this country, starting from the first day of the fall of Granada in the hands of the Spanish Christians in 1492. Perhaps in this research, we can take a brief look at the end of the Arab and Islamic presence in Andalusia during the period from the fall of Granada in 1492 until the final expulsion during the period 1614.